Forest Fire Disaster Management Actions: A Systematic Literature Review - Eva Gusmira; Aldri Frinaldi; Habibillah Alva Putra; Scendy Nawa Malini (Jurnal Ilmu Lingkungan, 2025)
Forest fires are events that can damage the environment with repeated occurrences due to changes in weather and climate. This incident must be found a solution to overcome it so as not to cause major losses to the community. This study was conducted to analyze mitigation measures in reducing the incidence of forest fires, variables that influence the occurrence of fires, and areas that are often the focus of several studies through literature reviews. This research approach uses a systematic literature review (SLR) with the Prisma method. Data sampling with Watase_Uake. Articles used with the Q1-Q4 index in the last 5 years, namely from 2019-2023. A total of 18 (eighteen) selected articles have gone through several specified processes. Generally, mitigation measures taken to overcome fires are by implementing government regulations through regulations, sanctions for violations, and approaches to the community. The variables that influence fires are climate variables, demographic changes, designing protocols to improve fire control, and alternative livelihoods that are socially just. The countries that are most often the objects of research are countries in the Asian region, especially Indonesia. This research has contributed to efforts to minimize forest fire incidents by looking at the variables that are factors that influence the role of government policy in dealing with them